DEPRESSION AND ANXIETY IN CORRELATION TO BODY AREAS INVOLVED IN PATIENTS OF BURNS - Ali, Ghazanfar; khan, Sikander Ali; Ahmed, Muzzafar; Malik, Muhammad Sheraz Afzal; Almas, Danish; Majid, Abdul (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the severity of depression and anxiety among patients of burns and correlate depression and anxiety with areas of body involved in burns.Study Design: A cross-sectional study.Place and Duration of Study: The departments of Psychiatry and department of Plastic Surgery, Combined Military Hospital Multan, from Oct 2019 to Mar 2020.Methodology: Through consecutive sampling, 56 patients of burns reporting to burns unit were assessed for anxiety and/ or depression based on the diagnostic criteria of International Classification of Diseases version 10. Symptom severity was assessed using Beck Depressive Inventory for depression and Beck Anxiety Inventory for anxiety. Descriptive statistics like mean with standard deviation was calculated for age. Frequency along with percentages was calculated for sociodemographic variables, Anxiety and depression.Results: Depression was present among 30 (53%) of participants out of which 16 (53.5%) had mild, 11 (37.9%) had moderate while only 3 (12.5%) had severe depression. Anxiety was seen among 50 (89%) of participants out of which sixteen (32.1%) had mild, 26 (51.7%) had moderate while 8 (16%) had severe anxiety. Significant correlation existed among the major area involved in burn with both anxiety and depression (p